2020
DOI: 10.1186/s13007-020-00624-2
|View full text |Cite|
|
Sign up to set email alerts
|

Early recognition of tomato gray leaf spot disease based on MobileNetv2-YOLOv3 model

Abstract: Background: Tomato gray leaf spot is a worldwide disease, especially in warm and humid areas. The continuous expansion of greenhouse tomato cultivation area and the frequent introduction of foreign varieties in recent years have increased the severity of the epidemic hazards of this disease in some tomato planting bases annually. This disease is a newly developed one. Thus, farmers generally lack prevention and control experience and measures in production; the disease is often misdiagnosed or not prevented an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(94 citation statements)
references
References 38 publications
0
94
0
Order By: Relevance
“…Previous studies have shown high accuracy under controlled laboratory conditions, but in complex light and complex background, the object detection results are not ideal and face many challenges [ 36 ]. Our previous work has achieved good results on the detection of a common gray leaf spot disease of tomato under natural conditions [ 37 ]. Chen et al [ 38 ] collected 8616 images containing five kinds of tomato diseases on the spot.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown high accuracy under controlled laboratory conditions, but in complex light and complex background, the object detection results are not ideal and face many challenges [ 36 ]. Our previous work has achieved good results on the detection of a common gray leaf spot disease of tomato under natural conditions [ 37 ]. Chen et al [ 38 ] collected 8616 images containing five kinds of tomato diseases on the spot.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of the era of big data, bioinformatics has been greatly improved 10 . This is a great help for our scienti c research.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in the original publication of the article [ 1 ], the symbol (+) was incorrectly mentioned as (=) in Equation 1.…”
Section: Correction To: Plant Methods (2020) 16:83 101186/s13007-020mentioning
confidence: 99%